Brief Report: Efficacy and Safety of Switching to a Single-Tablet Regimen of Elvitegravir/Cobicistat/Emtricitabine/Tenofovir Alafenamide in HIV-1/Hepatitis B–Coinfected Adults. (1st November 2016) - Gallant, Joel; Brunetta, Jason; Crofoot, Gordon; Benson, Paul; Mills, Anthony; Brinson, Cynthia; Oka, Shinichi; Cheng, Andrew; Garner, Will; Fordyce, Marshall; Das, Moupali; McCallister, Scott
Abstract : Abstract: Coformulated elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide (E/C/F/TAF) has high efficacy and improved renal and bone safety in multiple phase 3 trials; TAF single agent is being studied in 2 phase 3 trials in patients with chronic hepatitis B. We report the results of an open-label, noncomparative switch study evaluating the efficacy and safety of E/C/F/TAF in HIV/hepatitis B virus (HBV)–coinfected adults. At 48 weeks, 91.7% of the 72 participants maintained or achieved virologic suppression (HIV-1 RNA <50 copies/mL; HBV DNA <29 IU/mL). Seroconversion occurred in 2.9% of hepatitis B surface antigen–positive participants and in 3.3% of HBV e antigen–positive participants; 40% of those with abnormal alanine aminotransferase normalized. E/C/F/TAF was associated with improved renal function and reduced bone turnover. These data support the use of E/C/F/TAF in treating HIV/HBV coinfection.